The MIDA quantitative mortality risk score: prognostic model in floppy mitral valves. (14th October 2021) - Essayagh, B; Benfari, G; Antoine, C; Grigioni, F; Le Tourneau, T; Roussel, J C; Bax, J; Delgado, V; Ajmone, N; Van Wijngaarden, A; Tribouilloy, C; Hochstadt, A; et al.
Abstract: Background: The Mitral Regurgitation International Database (MIDA) score is a validated tool for Degenerative Mitral Regurgitation (DMR) management, being able to position a given patient within a continuous spectrum of short and long term mortality. However, whether this score may be applicable and incremental in the entire span of Floppy Mitral Valves (FMV), regardless of DMR severity, remains unsubstantiated. Methods: The MIDA-Quantitative (MIDA-Q) unprecedented registries include 8187 consecutive patients (age 64±17 years, 45% women, follow-up 5.5±3.4 years) with isolated degenerative mitral valve disease diagnosed at tertiary (European/ North-American/ Middle Eastern) centers in whom DMR severity used both integrative and quantitative grading. The MIDA-Q Score ranged from 0 to 15 depending on accumulating risk factors. Long-term survival overall, under medical management and post-mitral surgery was analysed. Results: By quantitative grading, MR was no/trivial in 1938 (24%), mild in 1423 (17%), moderate in 2027 (25%) and severe in 2799 (34%), with ERO 0.24±24cm 2, RVol 37±35mL, and posterior leaflet prolapse in 49%. MIDA-Q Scores stratified in 8 categories were 0 (score 0, n=851), 1 (score 1–2, n=1301), 2 (score 3–4, n=2043), 3 (score 5–6, n=1581), 4 (score 7–8, n=1273), 5 (score 9–10, n=718), 6 (score 11–12, n=331) and 7 (score 13–15, n=89). In the whole MIDA-Q population (n=8187 patients), 5-year survival under medical management with Scores categories 0–1, 2–4, and 5–7 was 96±1%, 73±1%, and 61±3% respectively (P<0.0001). Five-year mortality ranged from 3% with MIDA Q-score 0 to 95% with MIDA Q-score 13–15 (P<0.0001). After mitral surgery, 1-year mortality with Scores categories 0–1, 2–4, and 5–7 was 0%, 1%, and 6% respectively and 5-year post-operative survival was 99±1%, 94±1%, and 82±2% (all P<0.0001). In models including age, sex and all guideline-provided prognostic markers, the EuroScoreII and the MIDA Score without DMR severity, the MIDA-Q Score provided incremental prognostic information (P<0.001). Conclusion: This unheard international cohort of patients with FMV and prospective mitral severity quantitative grading, enables for the first time the calculation of a MIDA-Q Score, highly determinant of survival after diagnosis of FMV with any degree of DMR, that may be very useful for mitral valve prolapse management. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Mayo Fundation